Phosphate Metabolism in CKD Stages 3–5: Dietary and Pharmacological Control - Markus Ketteler (International Journal of Nephrology)
When compared to the available information for patients on dialysis (CKD stage 5D), data on the epidemiology and appropriate treatment of calcium and phosphate metabolism in the predialysis stages of chronic kidney disease (CKD) are quite limited. Perceptible derangements of calcium and phosphate levels start to become apparent when GFR falls below 30 mL/min in some, but not all, patients. However, hyperphosphatemia may be a significant morbidity and mortality risk predictor in predialysis CKD stages. The RIND study, evaluating progression of coronary artery calcification in incident hemodialysis patients, indirectly demonstrated that vascular calcification processes start to manifest in CKD patients prior to the dialysis stage, which may be closely linked to early and invisible derangements in calcium and phosphate homeostasis. Novel insights into the pathophysiology of calcium and phosphate handling such as the discovery of FGF23 and other phosphatonins suggest that a more complex assessment of phosphate balance is warranted, possibly including measurements of fractional phosphate excretion and phosphatonin levels in order to appropriately evaluate disordered metabolism in earlier stages of kidney disease. As a consequence, early and preventive treatment approaches may have to be developed for patients in CKD stages 3-5 to halt progression of CKD-MBD.